Global art exhibitions as ideals of geopolitical and social redefinition at the end of the 20th century - Ribeiro, Renata (2018)
Profound political, economic and social developments in the final decades of the 20th century changed the previously established foundations of the global geopolitical configuration. The system of art interpretation, a direct reflection of the power relations established at the other levels, was also permeated andinfluenced by these changes.